WAWASAN AL-QURAN TENTANG MANUSIA DAN LINGKUNGAN HIDUP SEBUAH KAJIAN TAFSIR TEMATIK - Muhammad Amin (Postgraduate State Islamic Institute (IAIN) Metro, 2016)
Al-Quran affirm that human as khalifah who has right to optimize the crops. However, some other people have different meaning to interpret this potential as the exploitation of crops exaggeratedly which resulted in the loss of ecosystem balance. This unbalance causes the various damages in the earth and cause the disaster. Al Quran has warned this condition and forbids people doing consumptive-exploitation. The researcher applied thematic interpretation approach in collecting the verses of Al Quran which explain about human and its relation with the environment. This research provide suggestion to apply Eco-Theologies interpretation as the practical interpretation to make human aware about the importance of environmental conservation.